2018
DOI: 10.17559/tv-20160702212234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graphite Additives on Mechanical, Tribological, Fire Resistance and Electrical Properties in Polyamide 6

Abstract: New types of polymers are usually produced with different additives. In this work, the effect of graphite addition (1.5wt%, 2wt%, 2.5wt%, 3wt% and 3.5wt%) on material's properties is analysed. Results of current investigation show that there are two possible subtypes (groups) of polyamide, containing 2% and 3.5% graphite, which reveal improved complex properties. By using graphite additives, the material becomes stiffer. In polyamide-2% graphite system, the abrasive wear tends to decrease while the fire resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…However, authors of work [6] showed that the use of antifriction fillers results in a significant reduction of strength and pore formation inside the volume of a polymer, which reduces operational characteristics of such PCMs. Although the introduction of graphite can significantly reduce the friction coefficient, as demonstrated in paper [7], the PCMs that are filled with layered lubricants cannot be operated under harsh conditions and in aggressive environments.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, authors of work [6] showed that the use of antifriction fillers results in a significant reduction of strength and pore formation inside the volume of a polymer, which reduces operational characteristics of such PCMs. Although the introduction of graphite can significantly reduce the friction coefficient, as demonstrated in paper [7], the PCMs that are filled with layered lubricants cannot be operated under harsh conditions and in aggressive environments.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Grafit, molibden disülfit (MoS2) ve politetrafloroetilen (PTFE) gibi bazı katı yağlayıcılar, mükemmel aşınma direnci ve düşük sürtünme özelliklerine sahiptir. Bu malzemeler, sıvı yağlayıcıların istenmediği ve etkisiz olduğu uygulamalarda tribolojik zorlukları çözmek için yaygın olarak kullanılmaktadır (Ben Difallah, Kharrat, Dammak ve Monteil, 2012;Ben Difallah, Kharrat, Dammak ve Monteil, 2014;Kumar & Kanagaraj, 2016;Matyas, 2018;Alajmi, Alrashdan, Alsaeed ve Shalwan, 2020). Bu malzemeler arasında, grafit, polimerlerin tribolojik, mekanik, termal ve elektriksel özelliklerini iyileştirmek için yaygın olarak kullanılan en önemli ve gelecek vaat eden katı yağlayıcılardan biridir (Raffaele, 2016;Dajana, Simon, Mitjan, Janez, Blaz ve Miroslav 2022;Ben Difallah et al, 2012).…”
unclassified